1995
DOI: 10.1111/j.1348-0421.1995.tb02185.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Production of Various Cytokines in Splenocytes of Sheep Erythrocyte‐Immunized Mice after Intravenous Administration of Bacterial Lipid A

Abstract: The effects of an intravenous administration of lipid A from Salmonella minnesota R595 lipopolysaccharide on the in vivo production of interleukin-2 (IL-2), IL-4, IL-5 and IL-6 in the spleens of mice intravenously immunized with sheep red blood cell (SRBC) antigen were investigated. The increased number of antigen-specific IgM antibody-producing cells and the titer of the IgM serum antibody were measured using the plaque-forming cell (PFC) assay and an enzyme-linked immunosorbent assay (ELISA). Simultaneous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The results suggest that sensitization protocol up regulates Th1 and Th2 cytokine production significantly as compared to unsensitized control (Tables 1 and 2). Such upregulation effect of SRBC on Th1 and Th2 cytokines is consistent with previous reports (Mashimo and Mita, 1995).…”
Section: Effect Of Sensitization Protocol On Selected Immune Markerssupporting
confidence: 93%
“…The results suggest that sensitization protocol up regulates Th1 and Th2 cytokine production significantly as compared to unsensitized control (Tables 1 and 2). Such upregulation effect of SRBC on Th1 and Th2 cytokines is consistent with previous reports (Mashimo and Mita, 1995).…”
Section: Effect Of Sensitization Protocol On Selected Immune Markerssupporting
confidence: 93%
“…We previously reported that orally injected PTCF strongly enhanced the splenic anti-sheep red blood cells (SRBC) plaque-forming cell (PFC) at the doses of 3-30 mg/kg/day [4]. The anti-SRBC PFC response is humoral and cellular immune responses requiring activation of B cells, T cells and monocytes [21], and the enhanced cytokines such as IL-2 [22], IFN-g [23], IL-4, IL-5 and IL-6 [24] correlate with PFC number and IgM titer. In this experiment, PTCF selectively triggered and potentiated IL-2 and IFN-g production in the PP cells (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…This may partly explain the results presented herein that show a single LPS injection induces significant suppression of antibody titers, but does not affect on the number of antibody producing spleen cells. Simultaneous injection of SRBC and lipid A from Salmonella Minnesota R595 enhances the number of IgM-plaque-forming spleen cells in mice 3 and 4 days after injection and the serum IgM titer 4 and 5 days after injection [7]. Thus, the timing of LPS injection may complicate the consequent immune response to particular antigens.…”
Section: Discussionmentioning
confidence: 99%